KOMPETENSI PROFESIONALISME GURU AKIDAH AKHLAK DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VIII MADRASAH TSANAWIYAH NEGERI 2 BATANG HARI - Tuti Hidayah; Fitri Nasution (Kampus Akademik Publiser, 2025)
This study aims to determine the Professional Competence carried out by teachers in improving student learning achievement at MTSN Batang Hari. To find out the obstacles faced by teachers in improving student learning achievement at MTSN 2 Batang Hari. The results of this study indicate that the professional competence of teachers in improving student learning achievement has been carried out but has not been optimal. Then the obstacle for teachers in improving learning achievement is that there are still students who chat during the learning process. Efforts made by teachers to overcome obstacles in improving learning achievement by giving appreciation/rewards to students, so that they are enthusiastic in improving learning achievement.